Beyond the token status: Women in business consultancies in Germany - Hedwig Rudolph (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
This article documents and analyzes the extent and structure of gender-related differences in employment conditions in the business consulting sector in Germany. Using a structural and actor-oriented approach, I tested the hypothesis that the (limited) career paths of women are attributable to the interaction of structural aspects of the sector and company-specific personnel policies. Analysis of the empirical material (e.g., interviews with executives in 40 consulting firms) points to the filter effects of structural factors (location, company size, consulting field, hierarchy level) as well as to certain components of corporate culture (performance assessment criteria, the role of informal networks, the ideology of extensive employee availability). Consequently, the main problem for women is not getting into business consulting, but coping with the substantial social costs of a long-term career in this field. – – Der Beitrag dokumentiert und analysiert Ausmaß und Struktur geschlechtsbezogener Unterschiede der Beschäftigungsbedingungen in der Branche Unternehmensberatung in Deutschland. Ausgehend von struktur- und akteursorientierten Ansätzen wird die These überprüft, dass die (begrenzten) Karrierewege von Frauen dem Zusammenspiel von strukturellen Merkmalen der Branche mit unternehmensspezifischen Personalpolitiken geschuldet sind. Die Auswertung der empirischen Materialien (u.a. Interviews mit Führungskräften in 40 Beratungsunternehmen) verweist auf die Filtereffekte von strukturellen Faktoren (Standort, Unternehmensgröße, Beratungsfeld, Hierarchie-Ebene), aber auch von Komponenten der Unternehmenskultur (Kriterien der Leistungsbeurteilung, Rolle informeller Netzwerke, Ideologie umfassender Verfügbarkeit). Somit erweist sich nicht der Zugang zur Branche als problematisch für Frauen, sondern die sozialen Kosten einer längerfristigen Karriere in diesem Feld.
Keywords: 300; Unternehmensberatung; Frauenerwerbstätigkeit; Erwerbsverlauf; Weibliche Führungskräfte; Frauenpolitik; Deutschland